Big data now : 2015 edition : current perspectives from O'Reilly Media. (O'Reilly Media, 2016)
Now in its fifth year, O'Reilly's annual Big Data Now report recaps the trends, tools, applications, and forecasts we've talked about over the past year. For 2015, we've included a collection of blog posts, authored by leading thinkers and experts in the field, that reflect a unique set of themes we've identified as gaining significant attention and traction. Our list of 2015 topics include: Data-driven cultures Data science Data pipelines Big data architecture and infrastructure The Internet of Things and real time Applications of big data Security, ethics, and governance Is your organization on the right track? Get a hold of this free report now and stay in tune with the latest significant developments in big data.